Hypnotic Susceptibility of Inpatient Adolescents - (:unkn) unknown (My University, 2015)
A substantial body of literature suggests hypnosis is an effective therapeutic intervention for adolescents who suffer from a wide variety of psychological troubles (Rhue & Lynn, 1991; Schowalter, 1994; Wester & Sugarman, 2007). As compared to adults, adolescents' openness to experiences along with their imaginative capacity uniquely primes them to benefit from hypnotherapy (Bowers & LeBaron, 1986). Many studies have shown adolescents to respond to hypnotic suggestions at high levels. However, minimal research has investigated adolescents' responsiveness to hypnotic interventions while they are receiving treatment in psychiatric settings. Thus, this study investigated if adolescents in psychiatric inpatient settings respond to suggestions similarly to adolescents in the general population. More specifically, it investigated whether hypnotic inductions were necessary to generate responsiveness to suggestions. In order to test these hypotheses, 167 adolescents (ages 13-17) were recruited from a major inpatient behavioral health hospital in the Midwest. Subjects were randomly assigned to either one group session of hypnosis (n=84) with a full hypnotic induction from the Waterloo-Stanford Group Scale: Form C (WSGC) scale of hypnotic susceptibility (Bowers et al., 1982) or a comparison group (n=83) which did not receive the hypnotic induction, but consisted of eye closure, simple guided relaxation and suggestions. Furthermore, adolescents' level of absorption and dissociation were investigated to examine their influence on responsiveness to suggestions. A between-group comparison showed the experimental condition had a higher score (M = 6.55, SD = 2.93) than the comparison group (M = 5.19, SD = 2.52) on behavioral measures, t(165) = 3.23, p
Keywords: Absorption; Adolescent; Group Therapy; Hypnosis; Inpatient; Psychiatric Hospital